Linguistic Landscapes A Comparative Study of Urban Multilingualism in Tokyo - Backhaus, Peter (Multilingual Matters, 2006)
Linguistic Landscapes is the first comprehensive approach to a largely under-explored sociolinguistic phenomenon: language on signs. Based on an up-to-date review of previous research from various places around the world, the book develops an analytical framework for the systematic analysis of linguistic landscape data. This framework is applied to a sample of 2,444 signs collected in 28 survey areas in central Tokyo. Analytical categories include the languages contained and their combinations, differences between official and nonofficial signs, geographic distribution, availability of translation or transliteration, linguistic idiosyncrasies, and the comparison of older and newer signs, among others. Combining qualitative and quantitative methods, the analysis yields some unique insights about the writers of multilingual signs, their readers, and the languages and scripts in contact. Linguistic Landscapes thus demonstrates that the study of language on signs has much to contribute to research into urban multilingualism, as well as the study of language and society as a whole
Description based on online resource; title from PDF title page (publisher's Web site, viewed 25. Jul 2018)
Keywords: Mehrsprachigkeit; Japan; Tokio; Hochschulschrift